2016
DOI: 10.1021/acs.nanolett.6b02742
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Li+ Tunnels in Core–Shell Li(NixMnyCoz)O2@LiFePO4 Enhances Its High Voltage Cycling Stability as Li-ion Battery Cathode

Abstract: Layered transition-metal oxides (Li[NiMnCo]O, NMC, or NMCxyz) due to their poor stability when cycled at a high operating voltage (>4.5 V) have limited their practical applications in industry. Earlier researches have identified Mn(II)-dissolution and some parasitic reactions between NMC surface and electrolyte, especially when NMC is charged to a high potential, as primarily factors responsible for the fading. In our previous work, we have achieved a capacity of NMC active material close to theoretical value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 42 publications
1
69
0
Order By: Relevance
“…Representative approaches include the doping, [86][87][88][89][90][91][92][93][94][95][96][97][98] morphological control of the primary particle, [99][100][101][102][103][104] the cathode surface modification, [105][106][107][108][109][110] and the primary particle coating, [35,37,[111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] which will be discussed below.…”
Section: Strategies To Realize Commercializationmentioning
confidence: 99%
“…Representative approaches include the doping, [86][87][88][89][90][91][92][93][94][95][96][97][98] morphological control of the primary particle, [99][100][101][102][103][104] the cathode surface modification, [105][106][107][108][109][110] and the primary particle coating, [35,37,[111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] which will be discussed below.…”
Section: Strategies To Realize Commercializationmentioning
confidence: 99%
“…12b) [97]. Researchers have also suggested that other types of cathode materials with more cycling stability can be used as coating materials such as LFP [186].…”
Section: X M Y O Z Coatingmentioning
confidence: 99%
“…Several strategies aiming at improving the performance and stability of Ni-rich NCM CAMs are currently pursued. [252][253][254][255][256] Also, molecular surface functionalization using organophosphates can apparently successfully reduce transition-metal dissolution, thereby positively affecting the cell cyclability. Bulk doping seems to be a viable strategy to enhance both the cycling performance and structural stability.…”
Section: Summary and Perspectivementioning
confidence: 99%